Perbandingan Pengaruh Aromaterapi Citrus Aurantium (Bitter Orange) dengan Aromaterapi Mawar terhadap Tingkat Kecemasan Ibu Bersalin Kala I Fase Aktif di RSUD Koja - Raden Nova Nurutami; Cholisah Suralaga; Vivi Silawati (Universitas Malahayati Lampung, 2025)
ABSTRACT Mothers in the active phase of labor usually experience anxiety due to discomfort due to contractions. One effort to reduce anxiety is by giving Citrus aurantium (bitter orange) Aromatherapy and rose Aromatherapy. Based on the results of interviews from 10 pregnant women who were carried out in the delivery room at the Koja City General Hospital in North Jakarta, it was found that all of them said they were worried about the delivery process. To determine the comparison of the effect of Citrus aurantium (bitter orange) Aromatherapy and rose Aromatherapy on the anxiety level of mothers during the first active phase of labor at Koja Hospital in 2023. Quasy experiment with pre-test and post-test two group design. The sample in the study was pregnant women whose estimated delivery was in June 2023 as many as 30 respondents using a purposive sampling technique. Data analysis used the paired sample t-test and Independent T-Test, which were previously tested for normality and homogeneity. The results of a univariate study showed that maternal anxiety during the first active phase before being given Citrus aurantium (bitter orange) Aromatherapy decreased with a difference in average value of 4.14. The anxiety of the mother during the first active phase before being given rose Aromatherapy decreased with an average difference of 1.07. The results of the bivariate study were paired sample t-test Aromatherapy of Citrus aurantium (bitter orange) (P Value 0.000) and Aromatherapy of roses (P Value 0.001). Independent T-Test test results with a P Value of 0.003.There is a difference in the effect of Citrus aurantium (bitter orange) Aromatherapy and rose Aromatherapy on the anxiety level of mothers during the first active phase. It is hoped that giving Citrus aurantium and rose Aromatherapy can be used as therapy for pregnant women who are experiencing anxiety. Keywords: Citrus Aurantium (Bitter Orange) Aromatherapy, Rose Aromatherapy, Maternity Anxiety ABSTRAK Ibu bersalin fase aktif biasanya mengalami kecemasan sehubungan dengan rasa tidak nyaman karena kontraksi. Salah satu upaya untuk mengurangi kecemasan adalah dengan memberikan aroma terapi Citrus aurantium (bitter orange)dan aroma terapi mawar. Berdasarkan hasil wawancara dari 10 ibu hamil yang dilakukan di ruang bersalin RSUD Koja Kota Jakarta Utara didapatkan seluruhnya mengatakan cemas akan proses persalinannya. Mengetahui perbandingan pengaruh aroma terapi Citrus aurantium (bitter orange) dengan aroma terapi mawar terhadap tingkat kecemasan ibu bersalin kala I fase aktif di RSUD Koja tahun 2023. Quasy experiment dengan rancangan pre-test and post-test two group design. Sampel dalam penelitian yaitu ibu hamil yang taksiran persalinannya pada bulan Juni 2023 sebanyak 30 responden dengan teknik purposive sampling, analisa data menggunakan uji paired sample t-test dan T-Test Independent yang sebelumnya dilakukan uji normalitas dan homogenitas. Hasil penelitian univariat kecemasan ibu bersalin kala I fase aktif sebelum diberikan aroma terapi Citrus aurantium (bitter orange) mengalami penurunan dengan selisih nilai rata-rata 4,14. Kecemasan ibu bersalin kala I fase aktif sebelum diberikan aroma terapi mawar mengalami penurunan dengan selisih nilai rata-rata 1,07. Hasil penelitian bivariat uji paired sample t-test aroma terapi Citrus aurantium (bitter orange) (P Value 0,000) dan aroma terapi mawar (P Value 0,001). Hasil uji T-Test Independent dengan P Value 0,003. Ada perbedaan pengaruh aroma terapi Citrus aurantium (bitter orange) dengan aroma terapi mawar terhadap tingkat kecemasan ibu bersalin kala I fase aktif. Diharapkan pemberian aroma terapi Citrus aurantium maupun mawar dapat dijadikan sebagai terapi pada ibu bersalin yang sedang mengalami kecemasan. Kata Kunci: Aroma Terapi Citrus Aurantium (Bitter Orange), Aroma Terapi Mawar, Kecemasan Ibu Bersalin